A market-oriented analysis of logistics services and perspectives on sustainability of a global manufacturer - Baumgartner, Matthias; Härdig, Johan; Joelsson, Axel; Johansson, Annie; Wingårdh, Hedda; Österberg, Oscar (My University, 2019)
In today’s global marketplace, customer expectations are high and expected to rise. Due to the increasing globalization and openness of markets, advanced and strategically sound logistics operations have become a necessity for companies wanting to remain competitive. Husqvarna Construction, a global distributor of light construction equipment, is subject to such a complex environment. They are currently facing problems regarding its logistics operations with high levels of inventory, a large number of backorders, and unsatisfied customers. The aim of this study is to identify the current and future demand for logistics services and perspectives on sustainability of Husqvarna Construction’s customers along with similarities and differences across the market. A thorough theoretical framework was created by a literature study of relevant fields. It covers theory regarding market orientation, market research, sustainability, logistics, and various trends within the field of study. Data was collected by both interviewing the supervisors at Husqvarna Construction and by distributing a survey to Husqvarna Construction’s customers within the European, Middle Eastern and African region. The main focus of the survey was to investigate the customers’ demand for logistics services within customer support, order management, warehouse, and transportation as well as their views on sustainability. Further, an analysis model was developed to act as a framework for the upcoming analysis. Husqvarna Construction’s customers showed similarities by placing the most value upon e- mail, e-commerce, and tracking as well as the importance of sustainability. The differences in demand between the customers were largely in terms of chat-support, kitting, bundling, drop shipment, and merge-in-transit. In terms of future demand, the customers were largely uncertain. The conclusion is that Husqvarna Construction should consider offering the services that show homogeneous patterns in terms of providing a high value and further investigate the potential benefits of providing the uniquely requested services.